ANALISIS FRAMING ISU SENGKETA 4 PULAU ACEH DI HARIAN SERAMBI INDONESIA - Asmaul Husna; Kamaruddin Hasan; Masriadi; Awaluddin Arifin; Muhammad Fazil (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
The territorial dispute over four islands: Mangkir Gadang, Mangkir Ketek, Lipan, and Panjang between Aceh and North Sumatra in early 2025 became a national polemic highlighting issues of boundary demarcation, cultural identity, and the dynamics of central regional relations. This issue received extensive media coverage, particularly in Harian Serambi Indonesia (SI), which plays a significant role in shaping public opinion in Aceh. This study aims to analyze how Serambi Indonesia frames the dispute over the four islands by applying Robert N. Entman’s framing analysis model, which encompasses four elements: define problems, diagnose causes, make moral judgements, and treatment recommendations. This research employs a descriptive qualitative approach, focusing on news texts. The findings reveal that Serambi Indonesia framed the issue by positioning North Sumatra as the party attempting to seize the four islands located in Aceh Singkil. Furthermore, the coverage highlighted the Ministry of Home Affairs (Kemendagri) as the main actor triggering the conflict, as it unilaterally designated the four islands as part of North Sumatra. In addition, the ministry was portrayed as neglecting the protests voiced by the Acehnese government and society against the decision. Eventually, the coverage concluded with the presidential decision affirming that the four islands rightfully belong to Aceh.